Knowledge on Sepsis among Health Care Providers of Birat Medical College and Teaching Hospital - Bajracharya, Akriti; Rajbanshi, Lalit Kumar; Arjyal, Batsalya (Birat Journal of Health Sciences, 2020)
Introduction: Knowledge and awareness of sepsis among various health care professionals is essential for prompt diagnosis and appropriate initial resuscitation and management of patient with sepsis.Objective: To assess and compare the knowledge and awareness of sepsis among health care professionals working at Birat Medical College and Teaching Hospital.Methodology This was a questionnaire-based survey with comparative study in 200 health care professionals conducted at Birat Medical College and Teaching Hospital from July– September, 2019. Questions were designed to assess the knowledge on diagnosis, initial resuscitation and management of sepsis. The knowledge level of the participants was assessed with scoring system as good, average and poor which was finally compared between the various health care professionals.Result Out of 200, only 180 health care professionals were included for statistical analysis. While assessing the knowledge on diagnosis of sepsis, 55.6% consultant doctors, 42.8% medical officers and 21.5% nursing/paramedics answered correctly on an average. Similarly, 51.7 % consultant doctors, 33.7% medical officers and 26.6% nursing/ paramedics gave correct answers while assessing knowledge on initial resuscitation and management. The nursing/paramedics had comparatively lower knowledge level on sepsis than the doctors. Around 31.7%, 51.2% and 17% of health care professionals working in Emergency, ICU and Anesthesiology departments had good, average and poor knowledge on sepsis respectively as compared to 14.2%, 28.5% and 57.1% of participants working in other departments.Conclusion: The nursing/paramedics had lower knowledge level on sepsis as compared to the doctors while health care professionals working in Emergency,ICU and Anesthesiology departments had better knowledge on sepsis as compared to staffs working in other departments.